Decreasing temperature sensitivity of spring phenology decelerates the advance of spring phenology in northern temperate and boreal forests - Tao Xiong; Shihong Du; Hongyan Zhang; Xiuyuan Zhang (Ecological Indicators, 2024)
The start of the growing season (SOS) plays a pivotal role in the intricate interplay between climate and terrestrial ecosystems. Since the late 1990 s, a slowdown in SOS advancing trend has been documented across numerous regions in the Northern Hemisphere. However, it remains uncertain whether a commensurate slowdown in the SOS advancing trend has manifested in northern temperate and boreal forests. Therefore, our effort is dedicated to unraveling the change in SOS both before and after the late 1990 s and to elucidate the underlying mechanisms causing this phenomenon. Our findings show that despite an overall increase in preseason temperature in northern temperate and boreal forests, an unexpected slowdown in the SOS advancing trend has occurred between 1999 and 2015, primarily due to a decrease in SOS temperature sensitivity. Furthermore, we have identified two distinct effects of preseason precipitation on SOS temperature sensitivity. As preseason precipitation increases, SOS temperature sensitivity experiences an increment of 0.34 days/°C∙10 mm, up to a preseason precipitation threshold of 70 mm, after which it undergoes a reduction at a rate of 0.12 days/°C∙10 mm. Our results provide valuable insights into understanding how SOS responds to ongoing climate warming in northern temperate and boreal forests. In addition, we have, for the first time, identified two distinct regulatory mechanisms governing SOS temperature sensitivity in relation to preseason precipitation before and after the 70 mm threshold, opening new avenues for the development of more accurate phenological models.